2003
DOI: 10.1016/s0304-4203(02)00139-1
|View full text |Cite
|
Sign up to set email alerts
|

Burial and reactivity of sedimentary microalgal lipids in bioturbated Mediterranean coastal sediments

Abstract: International audienceThe fate of microalgal lipid biomarkers in marine coastal sediments when acted on by natural bioturbation processes (Carteau Bay, Gulf of Fos, Mediterranean Sea) was studied under laboratory conditions. Both dead phytoplanktonic cells (Nannochloropsis salina) and luminophores (inert fluorescent particulate tracers) were deposited at the surface of intact sediment cores which were then incubated for 22, 44 and 63 days. Sediment reworking and concentration profiles of specific lipid compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 44 publications
2
20
1
Order By: Relevance
“…The degradation rate constants of individual (free+ esterified) FA were consistent with those calculated for individual lipids in previous studies performed under either experimental (Grossi et al, 2003, and references therein) or natural (Canuel and Martens, 1996) conditions. They were, however, one to three orders of magnitude higher than those generally observed in strictly anoxic sediments (Sun and Wakeham, 1994;Grossi et al, 2001Grossi et al, , 2003.…”
Section: Influence Of Oxygen On Tg Hydrolysis and Fa Degradationsupporting
confidence: 88%
See 3 more Smart Citations
“…The degradation rate constants of individual (free+ esterified) FA were consistent with those calculated for individual lipids in previous studies performed under either experimental (Grossi et al, 2003, and references therein) or natural (Canuel and Martens, 1996) conditions. They were, however, one to three orders of magnitude higher than those generally observed in strictly anoxic sediments (Sun and Wakeham, 1994;Grossi et al, 2001Grossi et al, , 2003.…”
Section: Influence Of Oxygen On Tg Hydrolysis and Fa Degradationsupporting
confidence: 88%
“…They were, however, one to three orders of magnitude higher than those generally observed in strictly anoxic sediments (Sun and Wakeham, 1994;Grossi et al, 2001Grossi et al, , 2003. Also, for the same FA under permanently oxic conditions Sun et al (2002) observed higher (3-4 times) degradation rates compared to the present case.…”
Section: Influence Of Oxygen On Tg Hydrolysis and Fa Degradationcontrasting
confidence: 65%
See 2 more Smart Citations
“…Off the Rhône River, surface and subsurface deposit-feeder species predominate, representing a link between continental POC and the marine food web (Harmelin-Vivien et al, 2009). Biogeochemical processes (burial and organic matter decomposition) are also directly affected by the benthic infauna that rework and irrigate the sediments (Grossi et al, 2003;Duport et al, 2007). However, high physical disturbance can decrease diversity (Hermand et al, 2008) and generally precludes macrofaunal biomass from dominating benthic communities in fluidized muds .…”
Section: Fate Of Sedimentary Fatty Acid In the Rhône Deltaic Systemmentioning
confidence: 99%